Superficial cervical plexus blockade improves pain control after thyroidectomy: A randomized controlled trial - Goulart, Taís Fonseca (2019)
OJECTIVES: The aim was to evaluate the ability of bilateral superficial cervical plexus blockade to control pain and to reduce the side effects of general anesthesia in patients submitted to thyroidectomy. METHODS: In this randomized controlled trial, we prospectively studied 100 consecutive patients who underwent total thyroidectomy. The simple random patient sample was divided into two groups: 50 patients received general anesthesia alone (group 1 [G1]), and 50 patients received general anesthesia with bilateral superficial cervical plexus blockade (group 2 [G2]). Statistical analyses were performed, and a 5% significance level was adopted. RESULTS: The mean arterial blood pressure and heart rate were 12% lower in G2 patients than in G1 patients 60 minutes after surgery (101 mmHg for G1 vs. 92.3 mmHg for G2; po0.001). G2 patients reported less pain than G1 patients, and opioid consumption was lower in G2 patients than in G1 patients, not upon postanesthesia care unit arrival, but at 30 minutes (2% vs. 34%; po0.001, respectively), 45 minutes (0% vs. 16%; p=0.006, respectively), and 4 hours postoperatively (6% vs. 20%; p=0.037, respectively). The incidence of nausea and vomiting was lower in G2 patients than in G1 patients from 45 minutes (0% vs. 16%; p=0.006, respectively) to 8 hours postoperatively (0% vs. 14%; p=0.012, respectively). CONCLUSIONS: The present study demonstrated that the combination of bilateral superficial cervical plexus blockade with general anesthesia for thyroidectomy is feasible, safe, and effective for achieving pain control and improving patient outcomes.